DETERMINATION OF COPPER IN ORANGE JUICE BY VOLTAMMETRIC TECHNIQUE: A COMPARATIVE STUDY OF SAMPLE PREPARATION METHODS - COULIBALY, Mariame; N’GUESSAN YAO, Alfred; BAMBA, Drissa; EL RHAZI, Mamia (Studia Universitatis Babeș-Bolyai Chemia, 2015)
In the present work, carbon paste electrodes (CPE) modified with conducting polymers (1,8-diaminonaphthalene, 1,8-DAN) combined with rotating disk electrode (RDE) was applied to determine copper in orange juice samples. Copper (II) was preconcentrated at open circuit potential on the modified electrode. Then, the preconcentrated metals were oxidized by scanning the potential of the electrode from -0.4 to 0 V using differential pulse anodic stripping voltammetry (DPASV). Samples were analyzed with and without previous treatment. The current peak was high in orange juice sample digested with wet ashing and dry ashing procedures compared to those in sample without pretreatment. The wet ashing procedure was chosen for the digestion of orange samples because it required a shorter time. The results obtained were validated by inductively coupled plasma atomic emission spectroscopy (ICP-AES).